Attitude control for tethered towing debris under actuators and dynamics uncertainty. Issue 6 (15th September 2019) - Jia, Cheng; Meng, Zhongjie; Huang, Panfeng
Abstract: Tethered towing is regarded as a promising debris removal technology to decrease the population of space debris. Owing to the debris rotation, the debris and tether are vulnerable to entanglement in the towing process. After capture, the untight capture leads to relative motion between gripper and debris and changes the actuator configuration matrix inevitably. Thus, except the traditional dynamics uncertainties, it is also necessary to consider the control allocation of multi-actuators under the nonnegative unilateral magnitude constraint and configuration matrix uncertainty. To tackle these problems, a novel scheme was proposed to stabilize the attitude of debris using adaptive backstepping control with robust allocation technique. Specifically, the adaptive attitude stabilization law is designed to generate control torques in the presence of dynamics uncertainties. A robust control allocation algorithm is developed to distribute the three axis torques to redundant actuators, in which the optimal control vector of actuator is obtained by interior-point method, under the actuator configuration matrix uncertainty and saturation constraints. Finally, numerical simulation results are employed to validate the effectiveness of the proposed scheme.